The Influence of Discovery Learning with Nearpod on Science Process Skills and Learning Outcomes - Permata, Citra; Kodri Madang; Susy Amizera (Program Studi Pendidikan Biologi Fakultas Ilmu Tarbiyah dan Keguruan Universitas Islam Negeri Raden Fatah Palembang, 2025)
Low science process skills and learning outcomes in digestive system topics stem from non-interactive learning. This study aimed to determine the influence of the Discovery Learning model assisted by Nearpod media on students’ science process skills and learning outcomes in the digestive system topic. A quasi-experimental non-equivalent control group design was used, involving two classes and analyzed via MANOVA/ANCOVA. MANOVA revealed significant influence on observation (0.313) and classification (0.716) indicators. The experimental group’s mean score rose from 60.40 to 83.60, outperfoming the control group (74.00). ANCOVA showed significance of 0.020 (p< 0.05). Nearpod assisted Discovery Learning significantly enhances students science process skills and learning outcomes.